2009
DOI: 10.1097/rli.0b013e3181b248f9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Dynamic Blood Oxygen Level-Dependent Magnetic Resonance Imaging of Foot and Calf Muscles

Abstract: Simultaneous BOLD-imaging of calf and foot muscles is feasible and reveals statistically significant age-related differences during ischemia and postocclusive hyperemia in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 40 publications
10
43
1
Order By: Relevance
“…14 Age-related changes in BOLD variables are still disputed 16,17 ; both these studies reported relatively low peak values in elderly subjects but contradictory findings for TTP. These 2 studies and the present study concur that mB can noninvasively distinguish non-PAOD and PAOD, the young and the elderly, and nonsmokers and smokers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 Age-related changes in BOLD variables are still disputed 16,17 ; both these studies reported relatively low peak values in elderly subjects but contradictory findings for TTP. These 2 studies and the present study concur that mB can noninvasively distinguish non-PAOD and PAOD, the young and the elderly, and nonsmokers and smokers.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,17,22 We applied a conventional sphygmomanometer air cuff for the thigh (86 © 21 cm; Welch Allyn Japan, Tokyo, Japan) to the middle of the left thigh (Fig. 1a) (40-s rest phase), compressed the cuff by applying pressure of 50 mm Hg above the individual's brachial systolic blood pressure to induce ischemia (300-s ischemic phase), and then rapidly reduced compression by opening the air valve, provoking reactive hyperemia (360-s hyperemic phase) (Fig.…”
Section: Cuff-compression Paradigm For Reactive Hyperemiamentioning
confidence: 99%
See 3 more Smart Citations